Externalizing disorders and environmental risk: mechanisms of gene–environment interplay and strategies for intervention. (September 2014) - Samek, Diana R; Hicks, Brian M
Although heritable, externalizing disorders have a number of robust associations with several environmental risk factors, including family, school and peer contexts. To account for these associations, we integrate a behavioral genetic perspective with principles of a developmental cascade theory of antisocial behavior. The major environmental contexts associated with child externalizing problems are reviewed, as are the processes of gene–environment interplay underlying these associations. Throughout, we discuss implications for prevention and intervention. Three major approaches designed to reduce child externalizing behavior are reviewed. Prevention and intervention programs appear to be most successful when they target individuals or communities most at risk for developing externalizing disorders, rather than applied universally. We end by commenting on areas in need of additional research concerning environmental influences on persistent externalizing behaviors.